Peran Insulin-like Growth Factor-1 dalam Patofisiologi Gangguan Pendengaran - Anggita Dwi Paramitha; Tri Umiana Soleha; Putu Ristyaning Ayu (CV. Jasa Sukses Abadi, 2019)
Sensorineural hearing loss (SNHL) is considered a disease that cannot be treated due to irreversible nerve damage. SNHL occurs due to damage to the inner ear/cochlea namely hair cells and supporting cells (HCs and SCs). Hair cells that carry the sound into neurochemical damage are triggered by ROS. There are several factors that affect hearing loss. Insulin-like growth factor-I (IGF-I) belongs to the family of insulin polypeptides, which play a central role in embryonic development and adult nervous system homeostasis by endocrine, autocrine, and paracrine mechanisms. IGF-I is the basis for regulation of cochlear development, growth, and differentiation, and its mutation is related to hearing loss. Low IGF-I levels have been shown to correlate with various human syndromes that show a hearing loss.